Energy scenario in Malaysia: Embarking on the potential use of hydrogen energy - Zakaria Z.; Kamarudin S.K.; Ikhmal Salehmin M.N.; Rosyadah Ahmad N.N.; Aminuddin M.A.; Hanapi I.H.; Osman S.H.; Mohamad A.A. (Elsevier Ltd, 2024)
Energy plays a crucial role in human life as it is necessary for survival and enables us to perform daily activities. The passage of time has driven progress, with various tools, machines, and devices created to facilitate human affairs. Everything is very dependent on Energy. Unfortunately, the prevalent reliance on fossil fuels as the primary energy source has resulted in an environmental disparity attributed to greenhouse gas emissions. Besides, the depletion of fossil fuel reserves is a long-term concern for nations involved in fossil fuel production including Malaysia, which necessitates a delicate equilibrium between escalating energy demands and escalating pollution levels. This review paper aims to highlight the potential of renewable energy based on green hydrogen in Malaysia. The energy scenario in Malaysia has been reviewed by discussing energy demand, current population, energy policy synopsis, conventional energy sources, carbon emissions, and the direction of renewable energy in Malaysia. Besides, the conceptual framework for hydrogen as renewable energy was discussed covering the hydrogen economy, production technology, storage, and energy production using green hydrogen. Finally, potential applications for using hydrogen energy have been presented so that the future direction of using this alternative energy can be well planned in Malaysia. 2023 Hydrogen Energy Publications LLC